Amrutikarana of Ayurvedic metallic preparations: A systemic review - Om Pandey; Prashant Bedarkar; Biswajyoti Patgiri (Journal of Ayurveda, 2022)
Objectives: Ayurvedic metallic preparations are always a concern for the safety issue. A special process was also designed in the ancient classics of Rasashastra to remove the blemishes of such metallic preparation known as Amrutikarana. Different materials and methods are elucidated for this purpose which modifies the efficacy and glance of the incinerated metals and minerals. Data Sources: Eighty one Ayurvedic classical text books and published research studies were searched in the context of Amrutikarana. Online search engines namely J gate, Google scholar, Pubmed, DHARA online and AYUSH research portal were used for data mining of published research works. Review Methods: References and studies including the methods of preparation, safety, efficacy or toxicity studies of 'Amrutikarana' or 'Amritikarana' of Ayurvedic Bhasma were reviewed. Results: Amrutikarana process was invariably seen in the contexts of Abhraka, Lauha and Tamra Bhasma only in few texts. Research articles show that there are various physico-chemical changes involved in this process along with variations in the elemental level of Fe, Cu, C, oxides and particle size. Pharmacological studies clearly support the claim that Amrutikarana helps in reducing the toxicity of metallic preparations. However, clinical data is not available in support of the increased efficacy by this process. Conclusion: Amrutikarana process of metallic Bhasma preparations is an important tool to counteract the possible ill effects by changing its physico-chemical property but the scientific published data still lacks the Standard manufacturing procedures of Amrutikarana for such Bhasma and efficacy evaluations on clinical grounds.